What Makes the Efficacy and Effectiveness of Multicultural Counseling? - Herdi, Herdi; Kartadinata, Sunaryo; Taufiq, Agus (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2019)
Today, multicultural counseling to be one of the most efficacy and effective helping professionals services in helping counselees achieve positive changes. But, critical question is what makes efficacy and effectiveness of multicultural counseling? The purpose of this study is to explore of the factors affecting the efficacy and effectiveness of multicultural counseling. This study used survey method. The participant included 30 pre-service counselor educators (master’s students) from Department of Guidance and Counseling in Universitas Negeri Jakarta. Data were collected using questionnaire that is Common Factors in Multicultural Counseling Scale in the form of Likert five-level scale. The data were analyzed with exploratory factor analysis. The results showed that there are two factors affecting the efficacy and effectiveness of multicultural counseling in the perspectives of pre-service counselor educators, named: (1) specific factors, such as: counseling approach and techniques and multicultural counseling competencies; and (2) common factors, such as: person of the counselor (wisdom) and counseling alliance. The implication is that counselor educators need to consider and develop these factors in Counselor Education and Supervision programs.